Benzimidazoles and benzoxazoles via the nucleophilic addition of anilines to nitroalkanes. Issue 14 (11th March 2015) - Aksenov, Alexander V.; Smirnov, Alexander N.; Aksenov, Nicolai A.; Bijieva, Asiyat S.; Aksenova, Inna V.; Rubin, Michael
Abstract : PPA-induced umpolung triggers efficient nucleophilic addition of unactivated anilines to nitroalkanes to afford benzoxazoles and benzimidazoles. Abstract : PPA-induced umpolung triggers efficient nucleophilic addition of unactivated anilines to nitroalkanes to produce N -hydroxyimidamides. The latter undergo sequential acid-promoted cyclocondensation with ortho -OH or ortho -NHR moieties to afford benzoxazoles and benzimidazoles, respectively.